Mountains touched with fire : Chattanooga besieged, 1863 - Sword, Wiley (New York : St. Martin's Press, 1995)
Historian Wiley Sword offers a richly detailed account that captures the vivid personalities behind the battle for Chattanooga. Grant, Thomas, Bragg, William Tecumseh Sherman, Phil Sheridan, William Rosecrans, Pat Cleburne, Jefferson Davis, Abraham Lincoln - all come alive in a narrative that combines furious battle action with behind-the-scenes political maneuvering and astute analysis. Sword's storytelling gifts are augmented by a wealth of contemporary sources - including diaries, letters, and other unpublished material - where generals, officers, soldiers, and politicians offer their perspectives. A saga of war, power, charged rivalries, and small cogs driving great events, Mountains Touched With Fire tells the absorbing story of a turning point in American history.
Includes bibliographical references (p. [407]-420) and index.
Keywords: Chattanooga, Battle of, Chattanooga, Tenn., 1863.